Obstáculos presentes en Modelación Matemática. Caso Ecuaciones Diferenciales en la formación de Ingenieros - Plaza-Galvez, Luis Fernando (Revista Científica, 2016)
By professional experience, it has been observed that the activities of Mathematical Modeling of phenomena and / or engineering processes in one Differential Equations course, have detected some obstacles by the students in the teaching - learning process, which has motivated its identification, being the purpose of this paper. Initially, researches on obstacles in mathematical context, engineering process and mathematical modeling have been mentioned. To carry out the solution of this problem, a survey was conducted with all students who took the Differential Equation course in Engineering programs at the Unidad Central del Valle del Cauca, in the period 2015-2, after performing modeling practices. This Study was carried out using open type questionnaire and its consequent analysis was with a qualitative approach using the grounded theory. Subsequently, the results of carried survey are mentioned, which led to detect different types of obstacles according their origin. Finally, this research will let improve modelling process within triad: student, education and teacher.